CLINICAL ASPECTS IN PROSTHETIC CONVENTIONAL REMOVABLE TREATMENT FOR ELDERLY PATIENTS - Dan Nicolae Bosînceanu; Dana Budală; Norina Consuela Forna (Romanian Society of Oral Rehabilitation, 2013)
Reconstructing the edentulous arches is a very serious issue for the elderly patient because of the difficulties that may occur during the process of making the dentures, re-establishing the vertical dimension, recovering the facial aspect modified with age, cleaning and maintaining the dentures, all problems due to the third age. Material and methods The study was conducted on a group of 46 patients, 19 men and 27 women, with complete or subtotal edentation, denture wears or not, with ages over 60 years old, average age being 70,3. Patients came in our clinic accusing previous treatments and asking for their optimization or for re-establishing the function of the stomatognat system. Results Statistics proves that from 46 examined patients, 24 of them had a stressed geroindex, 17 of them were near the normal limits and 5 were younger than their biological age. Conclusions Prosthetic treatment for the elderly must have an integrative concept and not a standard one, being necessary an individualized treatment for each patient and for every stage of the treatment being adjusted for the main reason the patient came in, adjusted to their general health, their oral hygiene and attitude towards the previous treatments.